2022
DOI: 10.1161/jaha.121.024883
|View full text |Cite
|
Sign up to set email alerts
|

Heart Transplantation in Children With Down Syndrome

Abstract: Background Children with Down syndrome (DS) have a high risk of cardiac disease that may prompt consideration for heart transplantation (HTx). However, transplantation in patients with DS is rarely reported. This project aimed to collect and describe waitlist and post– HTx outcomes in children with DS. Methods and Results This is a retrospective case series of children with DS listed for HTx. Pediatric HTx centers were identified by their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…5 N–P). The prevalence of congenital heart disease (CHD) in individuals with Down syndrome (DS) [ 25 ] provided additional context to support the proposition that ExCh21-driven 5-oxo-ETE posed adverse effects on human cardiac development. Seeking further validation, we embarked on a study that involved differentiating N and P hiPSCs toward mesoderm, cardiac progenitor cells, and cardiomyocytes, followed by bulk RNA-seq analysis at day 7 (T7) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 N–P). The prevalence of congenital heart disease (CHD) in individuals with Down syndrome (DS) [ 25 ] provided additional context to support the proposition that ExCh21-driven 5-oxo-ETE posed adverse effects on human cardiac development. Seeking further validation, we embarked on a study that involved differentiating N and P hiPSCs toward mesoderm, cardiac progenitor cells, and cardiomyocytes, followed by bulk RNA-seq analysis at day 7 (T7) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18 Rather, it is the perpetuation of medical biases and quality-of-life judgments that presumptively label specific populations poor transplant candidates or label their support systems insufficient, notwithstanding data demonstrating their ability to achieve successful transplant outcomes. 19 Variability in compliance assessments and psychosocial support criteria allows medical biases to persist and disproportionately impedes waitlist access to patients from underserved populations. 20 Low-income Medicaid patients are 2.6 times more likely to be labelled non-compliant as privately insured patients.…”
Section: Injustices In Organ Allocationmentioning
confidence: 99%
“…Among the forms of treatment, heart transplantation becomes an alternative, as children with DS have a high risk of developing heart anomalies. Currently there are no concrete conclusions that contraindicate transplantation, but studies have shown that as DS leads to several extracardiac comorbidities, such manifestations can affect post-transplant recovery, such as pulmonary hypertension, immunological dysfunction, obesity, risk of acute leukemia and autoimmune disorders (GODOWN et al, 2022).…”
Section: Introductionmentioning
confidence: 99%